Analisis Strategi Event Budaya Festival Lampion Waisak dalam Peningkatan Kunjungan ke Borobudur - Catherine Widjaja; Rendy Sarudin (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the cultural event strategy of the Waisak Lantern Festival in increasing tourist visits to Borobudur Temple. This annual festival combines spiritual values with cultural appeal. Although it successfully attracts thousands of visitors, challenges persist in expanding promotional reach and shifting the perception that the event is purely religious. The research employs a descriptive qualitative method through in-depth interviews, observation, and documentation. Data analysis is conducted using theory and source triangulation to assess the effectiveness of planning strategies, promotional efforts, and visitor experiences. Additionally, a SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats in the festival's implementation. The results indicate that digital promotion is effective in attracting tourists, particularly the younger generation. Strong visual content and user participation serve as key attractions. However, weaknesses remain in location management, information distribution, and inclusive communication for non-Buddhist participants. The study recommends enhancing inclusive promotional strategies, strengthening technical coordination on-site, and fostering cross-sectoral synergy to establish the festival as a sustainable cultural event.